Radiosynthesis of [18F]AV1451 in pharmaceutical conditions and its biological characteristics. (October 2017) - Salabert, Anne-Sophie; Fontan, Charlotte; Fonta, Caroline; Alonso, Mathieu; Loukh, Najat; Delisle, Marie Bernadette; Tafani, Mathieu; Payoux, Pierre
Abstract: In this study, we describe the radiosynthesis of [ 18 F]AV1451 in terms of its pharmaceutical quality and characterise its physical and biological properties. We performed an in vitro serum stability study in fresh human plasma and a plasma protein binding study. The radiochemical yield was 24% (decay corrected), and the product met all regulatory quality requirements. We found that this compound is stable in fresh human plasma and binds tightly to plasma proteins, especially lipoproteins. Graphical abstract: Highlights: We performed radiofluorination with a pyridyl trialkyl substituted ammonium salt derivative. Pharmaceutical quality of [ 18 F]AV1451 was determined. We observed plasma protein binding of [ 18 F]AV1451.